2016
DOI: 10.1002/asia.201600516
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Different Doped Metal Cations on the Physicochemical Properties and Catalytic Activities of Ce20M1Ox (M=Zr, Cr, Mn, Fe, Co, Sn) Composite Oxides for Nitric Oxide Reduction by Carbon Monoxide

Abstract: This work is mainly focused on investigating the effects of different doped metal cations on the formation of Ce20 M1 Ox (M=Zr, Cr, Mn, Fe, Co, Sn) composite oxides and their physicochemical and catalytic properties for NO reduction by CO as a model reaction. The obtained samples were characterized by using N2 physisorption, X-ray diffraction, laser Raman spectroscopy, UV/Vis diffuse reflectance spectroscopy, inductively coupled plasma atomic emission spectroscopy, X-ray photoelectron spectroscopy, temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Another major factor in the efficacy of CAQK-LIP-GFs/DTX@HP in treating SCI is the neuroprotection of GFs, including their local immune-modulatory action and effects in promoting neuronal plasticity 46 . It is widely acknowledged that a pronounced microglia/macrophage response is induced after SCI via the release of pro-inflammatory cytokines, nitric oxide (NO), and reactive oxygen species (ROS) by M1 macrophages 69 , 70 , which leads to ECM degradation, scar formation, neuron death and axon retraction 71 , 72 . Our data suggest that GFs likely promote tissue repair and ECM remodeling in part by inhibiting the spread of M1 macrophages and increasing the activation and/or proliferation of M2 macrophages during the early post-lesion phase.…”
Section: Discussionmentioning
confidence: 99%
“…Another major factor in the efficacy of CAQK-LIP-GFs/DTX@HP in treating SCI is the neuroprotection of GFs, including their local immune-modulatory action and effects in promoting neuronal plasticity 46 . It is widely acknowledged that a pronounced microglia/macrophage response is induced after SCI via the release of pro-inflammatory cytokines, nitric oxide (NO), and reactive oxygen species (ROS) by M1 macrophages 69 , 70 , which leads to ECM degradation, scar formation, neuron death and axon retraction 71 , 72 . Our data suggest that GFs likely promote tissue repair and ECM remodeling in part by inhibiting the spread of M1 macrophages and increasing the activation and/or proliferation of M2 macrophages during the early post-lesion phase.…”
Section: Discussionmentioning
confidence: 99%
“…A well-known method to notably enhance cerium oxide redox activity is the addition of 3d transition metals to its unit cell to form solid solutions with an ordered atomic arrangement [3,102]. For instance, it has been demonstrated that Ce 1−x M x O 2−y mixed oxides (where M = Cr [103,104], Mn [104][105][106], Fe [104,106], Co [104][105][106], Ni [105,106], Cu [107,108], Zr [109][110][111], La [112][113][114]) exhibit lower reduction temperatures than pure ceria. The incorporation of noble metals to ceria to generate Ce 1−x M' x O 2−y mixed oxides (M' = Ru [115], Rh [116,117], Pd [117,118]) has also demonstrated to efficiently promote reducibility of cerium ions and greatly decrease the reduction temperatures too [119].…”
Section: Fundamental Studiesmentioning
confidence: 99%
“…Various other ceria catalysts doped with copper or chromium have recently been reported [14, 21, 22, 61, 62] . Direct comparisons with other articles is difficult due to differences in reaction conditions such as catalyst loading and reactant flowrates or ratios, which widely vary between different research groups.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, for NO reduction, our Cu/Cr‐doped ceria nanorods performed slightly better at 150 °C but somewhat worse at 200 °C compared with a Cr‐doped ceria catalyst (Ce 20 Cr 1 O x ) or a 0.07 % each Cu/Cr deposited on ceria (Table 2). [22] In any case, the latter uses a pulsed cathodic arc plasma technique in vacuum, much more complicated than our hydrothermal approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation